2008
DOI: 10.1016/j.physbeh.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sexual experience and estrus on male-seeking motivated behavior in the female rat

Abstract: Ovariectomized (OVX) female rats were trained to traverse a straight alley and return to a goal box where they had previously encountered a male rat, a female rat or an empty goal box. The time required to run the alley was used as an index of the subjects' motivation to re-engage the goal box target. Subjects were tested in both estrus and non-estrus, first sexually naïve and then again after sexual experience. Female rats ran most quickly for a male target, most slowly for an empty goal box, and at intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In particular, nPGi-lesioned animals did not increase the number of mounts received, or increase the amount of time spent in the mating arena, as is typically observed in females following successive mating experiences (Nofrey et al, 2008). Similarly, ejaculation-return latencies were significantly longer in nPGi-lesioned animals.…”
Section: 0 Discussionmentioning
confidence: 68%
“…In particular, nPGi-lesioned animals did not increase the number of mounts received, or increase the amount of time spent in the mating arena, as is typically observed in females following successive mating experiences (Nofrey et al, 2008). Similarly, ejaculation-return latencies were significantly longer in nPGi-lesioned animals.…”
Section: 0 Discussionmentioning
confidence: 68%
“…For instance, in control subjects we would expect females to express significantly lower RT’s for a male target when in estrus compared to when not in estrus. Indeed, such a difference has previously been observed in ovariectomized females given exogenous hormone treatment to induce behavioral estrus (Nofrey et al, 2008). We did see the expected pattern in our results, whereby subjects expressed lower RT’s and higher PT’s for a male target when estrous vs .…”
Section: Discussionmentioning
confidence: 76%
“…This apparatus has been previously utilized to assess socio-sexual motivation in both male (López and Ettenberg, 2000, 2001, 2002; López et al, 1999) and female rats (López et al, 2007, 2009, 2010; Nofrey et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Rats provided the opportunity to traverse an alley and enter a goal box for the delivery of bilateral mPFC infusions of cocaine, exhibited faster running over trials in much the same way that animals do when running an alley for natural reinforcers (e.g., Beach and Jordan, 1956; Ettenberg and Camp, 1986; Ettenberg and Horvitz, 1990; Lopez et al, 1999; Nofrey et al, 2008). These results therefore compliment and extend the findings of previous investigators who have reported that rats will readily learn to lever-press for self-administration of cocaine directly into the mPFC (e.g., Goeders and Smith, 1983, 1984; 1993; Goeders et al, 1986; McBride et al, 1999; see review by Tzschentke, 2000).…”
Section: Discussionmentioning
confidence: 96%